-6(x+4)=-43

Simple and best practice solution for -6(x+4)=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+4)=-43 equation:



-6(x+4)=-43
We move all terms to the left:
-6(x+4)-(-43)=0
We add all the numbers together, and all the variables
-6(x+4)+43=0
We multiply parentheses
-6x-24+43=0
We add all the numbers together, and all the variables
-6x+19=0
We move all terms containing x to the left, all other terms to the right
-6x=-19
x=-19/-6
x=3+1/6

See similar equations:

| 151+6x+11=180 | | 4/3v+25=30 | | 2x+3(5x-7)=77 | | 9k+3=6+9k | | 1=7+x/14 | | 1.25y-1=2.33y-2 | | (3x-5)/6=2x-1 | | 1x+7=-1x+2 | | -3(y+4)=4y-5 | | (3(2x)-4)=2x+4 | | 3x+5x-2+4=18 | | 4x²+8x-1=0 | | 4x+2=-1x+6 | | 5=-7w+5(w-3) | | 1/3(15x-21)=1/4(20-32x) | | 16=10x+96 | | -2+3h=4h-9 | | x/|4x+12|=16 | | g/14=13 | | 7x+4+90=180 | | 5=-7w+(w-3) | | x+5=3x+5=75 | | -2(4x-13)-7=176 | | 18+3x=30+x | | -10=5+n | | 0.05=7.16x+35.85 | | -10+p=p-10 | | 2x-16=x-9=11 | | 8y+y=5y | | 2/5y-5=7 | | 8h-2=-9+7h | | 67x=350 |

Equations solver categories